CURRENT SITUATION AND PROBLEMS OF “DIGITALIZATION” IN UKRAINE - Dovbysh , Anatolii; Kotukh, Yevhen (Pressing Problems of Public Administration, 2021)
The article examines the features of digitalization in public administration, formulates the main cybersecurity directions. Modern “digital movement” means the introduction in the field of public administration of various methods of digitization, which are characterized by certain innovations by the authorities, the transparency processes inside the authorities, cooperation between last ones and citizens. More and more public organizations need to address important issues of their domestic policy, especiallythose related to the security of publicly available online data and information, and increasingly organize close cooperation between various officials and employees, as well as with members of the community.Taking into account the complex scientific and methodological analysis, some features of theorganization of communication of public administration bodies depending on the level and size ofthe organization are highlighted. The current situation with cybersecurity is analyzed, as well asways to increase its level in the field of public administration in Ukraine. It is proved that the level ofdigitalization and informatization, and, accordingly, the development of e-government is low. Thereasons for this are:– unsatisfactory material and technical support of public administration bodies, in particular,obsolescence of computer and organizational equipment;– lack of high-speed Internet, especially in small towns, villages and hamlets;– insufficient level of knowledge, skills and abilities most in demand in the field of electronicdocument management technologies and secure online communication technologies, due to thelow level of awareness of cybersecurity modern means.The priority ways to increase the level of cybersecurity in the public sector in moderncircumstances should be increasing budget funding in the relevant field, strategic investment incyber analytics and cloud technologies, the creation of special units for cybersecurity, installationof modern software and its permanent updating, regular training of all employees in the field oforganizational and personal information protection of.